Art and art history - González, Beatriz (Estudios de Filosofía, 1996)
The answer to the question about the main characters of the History of art includes several candidates: the artist, the work of art, the historian, the critic and, even, the philosopher. However, the critic is not interested in history but in the immediate consideration of certain works of art. The historian, on his turn, is inclined to highlight in the works of art other values than the aesthetic ones. The bleacher depends on the work of the artist, the critic and the historian although he might not be identifiedwith any of them. Four models of the History of art derive from this: The model of Vasari where the artist is the core; that of Winckelmann where style is the essential; that of Wölfflin where the form is privileged and finally the model of Gombrich where the attention is focused on the work of art.